2015
DOI: 10.1007/s00348-015-1993-8
|View full text |Cite
|
Sign up to set email alerts
|

The time-resolved natural flow field of a fluidic oscillator

Abstract: the results infer that the jet's oscillation pattern is approximately sinusoidal with comparable residence and switching times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 17 publications
(29 reference statements)
5
45
0
Order By: Relevance
“…As already presented in many of the studies on FO, see for example [17][18][19][21][22][23]32], the MC and FC internal flow configuration along a complete oscillation period was divided in several equally spaced time steps. In the present study, the streamlines and pressure contour plots at Reynolds number 16,034 are divided into six time steps, which correspond to 1/6 of a typical oscillation period.…”
Section: Original Fluidic Oscillator At Reynolds Number 16034mentioning
confidence: 99%
See 1 more Smart Citation
“…As already presented in many of the studies on FO, see for example [17][18][19][21][22][23]32], the MC and FC internal flow configuration along a complete oscillation period was divided in several equally spaced time steps. In the present study, the streamlines and pressure contour plots at Reynolds number 16,034 are divided into six time steps, which correspond to 1/6 of a typical oscillation period.…”
Section: Original Fluidic Oscillator At Reynolds Number 16034mentioning
confidence: 99%
“…From their applications in flow control, it is interesting to mention their use in combustion control [3], flow deflection and mixing enhancement [4], flow separation modification in airfoils [5], boundary layer modification on hump diffusers used in turbomachinery [6], flow separation control on compressors stator vanes [7], gas turbine cooling [8], drag reduction on lorries [9], and noise reduction in cavities [10].Despite the existence of particular fluidic oscillator configurations, like the one introduced by Uzol and Camci [11], which was based on two elliptical cross-sections placed transversally and an afterbody located in front of them, or the one proposed by Huang and Chang [12], which was a V-shaped fluidic oscillator, most of the recent studies on oscillators focused on two main, very similar, canonical geometries, which Ostermann et al [13] called the angled and the curved oscillator geometries. Some very recent studies on the angled geometry are [13][14][15][16][17][18][19][20][21][22][23], while the curved geometry was studied by [4,10,13,[23][24][25][26][27][28][29][30][31][32][33]. Ostermann et al [13], compared both geometries, concluding that the curved one was energetically the most efficient.One of the first analyses of the internal flow on an angled fluidic oscillator was undertaken by Bobusch et al [17].…”
mentioning
confidence: 99%
“…These devices are used for active flow control applications, where the sweeping motion of the jet allows a much wider actuator spacing, resulting in less energy consumption (Woszidlo et al 2014). The data presented here stem from an experimental set-up investigating the spreading and entrainment of sweeping jets (Ostermann et al 2015b;Woszidlo et al 2015). The data are recorded at a Reynolds number of 37 000 based on the nozzle diameter D and the mean velocity in the nozzle.…”
Section: Fluidic Oscillatormentioning
confidence: 99%
“…A linear regression line emphasizes the linear dependency between the oscillation frequency and the jet velocity. This linear dependency is a consequence of the oscillator's internal flow dynamics, which is discussed in detail by Woszidlo et al (2015). The linear relationship is limited to the subsonic flow regime as it is present for all supply rates in this study.…”
Section: Relationship Between Velocity Ratio and Strouhal Numbermentioning
confidence: 76%
“…One type of a fluidic oscillator, similar to that used in this study for generating a spatially oscillating jet, is shown in figure 2. More details on the working principle of this design of fluidic oscillators are provided by Woszidlo et al (2015) and Sieber et al (2016). It is noteworthy that several modifications of this concept exist.…”
Section: Introductionmentioning
confidence: 99%